Eccentric Domination in Boolean Graph BG2(G) of a Graph G - et. al., M. Bhanumathi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Let G be a simple (p, q) graph with vertex set V(G) and edge set E(G). BG2(G) is a graph with vertex set V(G) È E(G) and two vertices are adjacent if and only if they correspond to two adjacent vertices of G, a vertex and an edge incident to it in G or two non-adjacent edges of G. In this paper, we studied eccentric domination number of Boolean graph BG2(G), obtained bounds of this parameter and determined its exact value for several classes of graphs.